(untitled) (International Seven Journal of Health Research, 2024)
Chronic myeloid leukemia (CML) occurs when the pluripotent stem cell undergoes malignant transformation and clonal myeloproliferation, causing overproduction of mature and immature granulocytes. Initially asymptomatic, the progression of chronic myeloid leukemia is insidious, with a non-specific "benign" stage (weakness, anorexia, weight loss), it ends up paving the way for an accelerated or blast phase with more dangerous signs, such as splenomegaly, pallor, easy bruising and bleeding, fever, lymphadenopathy and skin changes.